Two sides of the same coin: a complex presentation of autosomal dominant tubulointerstitial kidney diseases: a literature review and case reports - Fistrek Prlic, Margareta; Huljev Frkovic, Sanda; Beck, Bodo; Tonkovic Durisevic, Ivana; Bulimbasic, Stela; Coric, Marijana; Lamot, Lovro; Ivandic, Ema; Vukovic Brinar, Ivana (Frontiers in Pediatrics, 2023)
Introduction: Genetic kidney diseases are underdiagnosed, and hereditary tubulointerstitial kidney diseases, including autosomal dominant tubulointerstitial kidney diseases (ADTKD), are even more challenging to diagnose. ADTKD is a rare form of genetic kidney disease resulting from pathogenic variants in the MUC1, UMOD, HNF1B, REN, SEC61A1, and DNAJB11 genes. There is no typical clinical or histopathological sign of ADTKD. Usually, serum creatinine levels are elevated with no proteinuria, and the urinary sediment is bland. End-stage renal disease (ESRD) develops at the average age of 45, but this can be very variable. A family history that suggests autosomal dominant inheritance and CKD fulfilling the clinical characteristics of tubulointerstitial kidney disease should raise suspicion of ADTKD. Contrary to the aforementioned characteristics of ADTKD, in the case of HNF1B-related disease, there is a more complex clinical presentation with extrarenal manifestations of the disease. The diagnosis of ADTKD is based on a positive family history and the detection of the pathogenic variant in one of the genes in an affected individual. Aim: The aim of our study is to present two case reports of ADTKD with different characteristics (slowly progressive CKD vs. complex clinical presentation with an extrarenal manifestation of the disease) with a literature review. Methods: A 34-year-old patient with CKD and a positive family history of CKD in whom kidney biopsy showed nonspecific chronic changes, with only genetic analysis confirming the diagnosis of MUC1-related ADTKD. Our second case is of a 17-year-old patient with an unremarkable family history who was initially referred to genetic counseling due to cognitive and motor impairment with long-lasting epilepsy. An extensive workup revealed increased serum creatinine levels with no proteinuria and bland urinary sediment, along with hypomagnesemia. His genetic analysis revealed 17q12 deletion syndrome, causing the loss of one copy of the HNF1B gene, the AATF, and the LHX1 gene. Conclusion: Autosomal dominant tubulointerstitial kidney diseases are challenging to diagnose due to a lack of typical clinical or histopathological signs as well as an uncharacteristic and versatile clinical presentation. Increased clinical awareness is crucial for the detection of these diseases.